2007
DOI: 10.1016/j.jbiomech.2006.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Predictive modelling of human walking over a complete gait cycle

Abstract: An inverse dynamics multi-segment model of the body was combined with optimisation techniques to simulate normal walking in the sagittal plane on level ground. Walking is formulated as an optimal motor task subject to multiple constraints with minimisation of mechanical energy expenditure over a complete gait cycle being the performance criterion. All segmental motions and ground reactions were predicted from only three simple gait descriptors (inputs): walking velocity, cycle period and double stance duration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
131
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(136 citation statements)
references
References 19 publications
1
131
1
3
Order By: Relevance
“…constant success can be achieved with a number of techniques) and so the preferred technique might well be to adopt a minimal effort or energy strategy (e.g. walking, Ren, Jones and Howard, 2007). However, if the task is more complex, like the upstart (where the gymnast must remain within strength and anatomical limits, must arrive in a predetermined orientation and configuration and where the gymnast must perform correct actions at a correct time despite the presence of noise in the motor system) it might be that the solution space is so small that it effectively defines the technique.…”
Section: Discussionmentioning
confidence: 99%
“…constant success can be achieved with a number of techniques) and so the preferred technique might well be to adopt a minimal effort or energy strategy (e.g. walking, Ren, Jones and Howard, 2007). However, if the task is more complex, like the upstart (where the gymnast must remain within strength and anatomical limits, must arrive in a predetermined orientation and configuration and where the gymnast must perform correct actions at a correct time despite the presence of noise in the motor system) it might be that the solution space is so small that it effectively defines the technique.…”
Section: Discussionmentioning
confidence: 99%
“…Minimising effort (joint torques) or energy has been used to describe the underlying technique of everyday activities such as walking (Ren, Jones & Howard, 2007;Anderson & Pandy, 2001). When optimising sporting movements minimising joint torque has also been used with varying degrees of success (Hiley & Yeadon, 2012;Koschorreck & Mombaur, 2012;Yamasaki, Gotoh & Xin, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Simulation studies on gait have used models such as the triple rocker (Perry, 1992), polynomial fits (Ju and Mansour, 1988;Ren et al, 2007) and COP-based fits (Koopman et al, 1995;Srinivasan et al, 2008). McGeer (1990) used circular arcs for the plantar surface of the foot in passive dynamic walkers, and Vanderpool et al (2008) found that rolling feet are energetically efficient and can account for the loss of ankle motion.…”
Section: S Mohan Varma and S Sujatha: Segmental Contributions Tomentioning
confidence: 99%
“…Unlike other optimization-based inverse models (Koopman et al, 1995;Ren et al, 2007) in which optimization is used in parallel with the inverse model to predict the kinematics, kinetics or both, here optimization is used only to correct any errors in data that cause violation of the kinematic constraints. The effects of using the FROS and AFROS ) models on the GRF computations are studied.…”
Section: S Mohan Varma and S Sujatha: Segmental Contributions Tomentioning
confidence: 99%
See 1 more Smart Citation